The emerging role of ubiquitin-proteasome system dysfunction in the pathogenesis of perioperative neurocognitive disorders: a narrative review - Ma, Minghua; Yang, Jing; Yang, Yuan; Li, Lin (Frontiers in Behavioral Neuroscience, 2026)
Perioperative neurocognitive disorder (PND) is a prevalent and serious complication affecting the central nervous system following surgery, particularly among elderly patients. PND has a significant impact on patient prognosis and places a substantial burden on both individuals and the healthcare system. Despite its importance, the complex pathological mechanisms underlying PND remain inadequately understood, and there are currently no effective prevention or treatment strategies available. One critical factor contributing to PND is the imbalance in protein homeostasis, with the ubiquitin-proteasome system (UPS), recognized as the primary mechanism for protein quality control within cells. This review systematically discusses the crucial role of UPS dysfunction in the development of PND. Additionally, it analyzes potential biomarkers for diagnosing PND and explores treatment strategies targeting the UPS. This provides a new perspective for a deeper understanding of the molecular mechanisms involved in PND and lays a theoretical foundation for the development of new intervention methods.